Strategi Komunikasi Krisis Digital Personal dalam Kasus Pengadaan Chromebook: Analisis Klarifikasi Nadiem Makarim - Arief Rahmatullah, Firza; Irsyadi, Muhammad Tsani (Da'watuna: Journal of Communication and Islamic Broadcasting, 2026)
This study analyzes the personal digital crisis communication strategy employed by Nadiem Makarim in responding to legal accusations related to the Chromebook procurement policy during his tenure as Indonesia’s Minister of Education, Culture, Research, and Technology. This case is significant because it illustrates how a public figure uses digital channels to construct clarity amid legal pressure, media coverage, and rapidly evolving public perceptions in digital spaces. The study applies a descriptive qualitative approach using a case study method. Data were collected through document analysis of the White Paper published on Faktanadiem.org, Google’s official blog statements, and national media coverage presenting both the prosecution narrative and subsequent clarifications. The analysis is framed through Situational Crisis Communication Theory (SCCT), Image Restoration Theory, and Framing Theory. The findings reveal three dominant communication patterns: the centralization of clarification through a dedicated digital portal, the separation of narratives between personal identity, corporate relations, and public policy, and the reframing of the issue from alleged state financial loss and corruption toward a policy-based narrative. The study also finds that the effectiveness of personal digital crisis communication remains limited when initial public perception has already been shaped by legal legitimacy and reinforced by media framing. Therefore, personal digital crisis communication requires not only speed and transparency but also a credible, consistent narrative architecture capable of addressing the complex intersections between public figures, policy, and corporate interests.